2014
DOI: 10.3748/wjg.v20.i37.13382
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of choledocholithiasis in the golden age of imaging, endoscopy and laparoscopy

Abstract: Biliary lithiasis is an endemic condition in both Western and Eastern countries, in some studies affecting 20% of the general population. In up to 20% of cases, gallbladder stones are associated with common bile duct stones (CBDS), which are asymptomatic in up to one half of cases. Despite the wide variety of examinations and techniques available nowadays, two main open issues remain without a clear answer: how to cost-effectively diagnose CBDS and, when they are finally found, how to deal with them. CBDS diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
131
0
43

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(217 citation statements)
references
References 200 publications
4
131
0
43
Order By: Relevance
“…The strategy to be adopted will largely depend on local availability of surgical and endoscopic skills. Concerning CBD stones diagnosis, IOC, MRC and EUS are reported to have similar results [21].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The strategy to be adopted will largely depend on local availability of surgical and endoscopic skills. Concerning CBD stones diagnosis, IOC, MRC and EUS are reported to have similar results [21].…”
Section: Discussionmentioning
confidence: 78%
“…Low-risk patients do not require further examination before laparoscopic cholecystectomy. Those with a moderate or high risk require further diagnostic tests [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Although common bile duct (CBD) stones may be silent but it can often lead to biliary colic, cholangitis, jaundice, or pancreatitis. There are various techniques available for the visualization of biliary tree Costi et al (9) reported that ERCP after having been widely used for CBD stones diagnosis in the late eighties/nineties. ERCP is nowadays being progressively abandoned as a diagnostic tool for patients with moderate to intermediate risk of carrying CBD stones, as most cholangiograms result as being normal and ERCP is not costeffective.…”
Section: Discussionmentioning
confidence: 99%
“…Toda conducta encaminada al tratamiento de complicaciones, incrementa el costo asistencial y social (SANTO et al, 2012;BARRETO et al, 214;INEC. 2011;COSTI et al, 2014;GRINIATSOS et al, 2016).…”
Section: Introductionunclassified